2008
DOI: 10.1002/pssa.200824016
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the thermally quenched glow‐curve of Al2O3:C

Abstract: The experimental glow‐curve of Al2O3:C is highly disturbed due to the strong thermal quenching effect present in this material. Therefore, the real glow‐curve shape of this material is unknown. The present work describes an attempt to reconstruct the glow‐curve shape of Al2O3:C samples with different TL peak structures. The reconstruction procedure is performed in two steps. In the first step, the very narrow glow‐curves are fitted with the product of known kinetic equations and the expression giving the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
(9 reference statements)
1
11
0
2
Order By: Relevance
“…A direct curve fitting using Eq. (13) is not practical and is limited only to single TL peaks, provided that in the temperature region of the TL glow‐peak the η ( T ) values are not too low 16. It is, therefore, useful to examine how well the analytical expression I ( T ) can fit a thermally quenched glow‐peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct curve fitting using Eq. (13) is not practical and is limited only to single TL peaks, provided that in the temperature region of the TL glow‐peak the η ( T ) values are not too low 16. It is, therefore, useful to examine how well the analytical expression I ( T ) can fit a thermally quenched glow‐peak.…”
Section: Resultsmentioning
confidence: 99%
“…(1) to zero, it is found that the value of thermal quenching efficiency at its maximum variation rate (in absolute values) is given by: where T nm is the temperature of the maximum $|\eta _{\rm m} |$ . Since, usually it is $kT_{{\rm nm}} \ll W$ , it was found by Dallas et al 16 that $n_{\rm m} = 0.54 \pm 0.007$ for every W , C pair. This value of n m is useful for selecting the simulated glow‐peaks.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…При этом уширение пика происходит в сторону более высоких температур, что вызывает смещение в высокотемпера-турную область положения его максимума. В ряде об-разцов кривая ТЛ имеет ярко выраженную двухпиковую структуру [5][6][7].…”
Section: Introductionunclassified
“…Есть мнение, что основной пик может быть обусловлен равномерным распределением лову-шек по энергии, ширина которого коррелирует с по-лушириной пика [4]. Аппроксимация широкого ТЛ-пика уравнением общего порядка кинетики, учитывающим две ловушки, была проведена другими авторами [6]. В работе [7] было показано, что в образцах с узкими и уширенными ТЛ-пиками наблюдаются различия в до-зовых зависимостях параметров ТЛ.…”
Section: Introductionunclassified
“…For many TL materials this way is not suitable because of low TL sensitivity or complicated schemes of TL processes that can involve additional channels of electron transfer 6. Therefore, a number of methods for the evaluation of the TQ parameters based on an analysis of a series of TL glow curves recorded with variable heating rates were proposed 9–12.…”
Section: Introductionmentioning
confidence: 99%